(3GddHGH aj eNJUQ EMjGA Ydhe GdOjfs - (3eLO GdOjf CHh GdaJhM CMeO Hf eMeO Hf eMeO GdZRGdj, eLO GdOjf CMeO GdZRGdj,J (B520 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efhQ bdhH Cgd GdEjeGf HMbGFb GdCSQGQ heRjf SQGFQge HCfhGY GdCfhGQ s
(3BNQgG (B:s
(3hgPG BNQ eG cJHfGg ef eNJUQ EMjGA Ydhe GdOjf hGdMeO ddg hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3GdfSNI HgG MhGTs
(3Ydi dhMI GdYfhGf hbajIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs